Changes in hedonic hunger and food reward after a similar weight loss induced by a very low‐energy diet or bariatric surgery. Issue 10 (31st August 2022) - Aukan, Marthe Isaksen; Brandsæter, Ingrid Øfsti; Skårvold, Silje; Finlayson, Graham; Nymo, Siren; Coutinho, Silvia; Martins, Catia
Abstract: Objective: The aim of this study was to compare changes in hedonic hunger and food reward in individuals with severe obesity achieving 10% to 15% weight loss with a very low‐energy diet (VLED) alone or VLED and bariatric surgery. Methods: Patients scheduled for sleeve gastrectomy (SG) or Roux‐en‐Y gastric bypass (RYGB) initiated a VLED 2 weeks prior to surgery and continued the diet for 8 weeks postoperatively. BMI‐matched controls underwent a VLED for 10 weeks. Hedonic hunger was assessed with the Power of Food Scale, and food reward with the Leeds Food Preference Questionnaire, pre and post intervention. Results: A total of 44 participants completed the study: 15 SG, 14 RYGB, and 15 controls (61%, 79% and 69% females, respectively; BMI: 40.5 ± 0.5 kg/m 2 ; age: 43.9 ± 1.4 years). Average weight loss was 18.3 ± 0.6 kg (16%), comprising 13.5 ± 0.5 kg fat mass, with no significant differences between groups. Similar reductions in hedonic hunger were observed in all groups. Overall, food reward was similarly reduced in SG and RYGB groups, whereas controls showed little or no change. Conclusions: Independent of modality, weight loss seems to reduce hedonic hunger, but bariatric surgery leads to several additional favorable changes in food reward and preferences.